EHIT after thermoablation - Di Mitri, R.; Leo, M.; Romano, R. (Phlebologie, 2017)
Aim: After 10 years of experience, we evaluated the incidence and management of endothermal heat-induced-thrombosis (EHIT), i.e. saphenous vein thrombosis following endothermic treatment of saphenous vein re-flux.Methods: From 2006 to 2016 data were retrospectively collected on 840 patients undergoing saphenous vein treatment by laser and radiofrequency technique. All patients were treated with tumescent local anaesthesia in an ambulatory setting to promote early mobilization. Class II compression stockings and heparin were recommended for 5 days post-operatively.Results: EHIT was observed in 15 patients from a total of 992 saphenous veins which were evaluated (1,5 %). 14 patients treated by EVLA had EHIT 1, one patient by RFA had EHIT 2, complicated by pulmonary embolism. All EHIT patients were treated by low weight molecular heparin. 980 nm laser and bare-tip fibres had been used in EVLA-EHIT patients. EHIT was not observed in patients treated by 1470 nm laser and radial fibres.Conclusions: Latest generation technology, the ambulatory setting and local anaesthesia probably contributed to the low incidence of EHIT reported. Further studies are necessary for a better acquaintance of these complications and to facilitate the development of specific guidelines.
Keywords: EHIT; thrombosis; thermoablation; endovascular